Reviewing the Three-Sentence Story Writing Training Program (Tatika) in Raising Literacy Interests of Middle School Students - Nida Amalia Manggala; Yaya Sunarya (al-Afkar, Journal For Islamic Studies, 2025)
The low literacy rate of Indonesians was the background for the government to launch the School Literacy Movement (GLS) program in 2016 with the hope of improving students' literacy culture in schools. This study aims to determine the impact of one of the School Literacy Movement programs at SMPN 39 Bandung, namely the Three-Sentence Story Writing Training (Tatika) on the reading and writing interests of SMPN 39 Bandung students. The method used in this study is a qualitative method. Data collection techniques used were interviews with the principal and teachers as the implementing committee for the Tatika program, distributing questionnaires, and field observations. Based on the results of the study, with the holding of the "Three-Sentence Story Writing" training at SMPN 39 Bandung, there was an increase in the reading and writing interests of SMPN 39 Bandung students as seen from the increasing number of library visitors and the enthusiasm of SMPN 39 Bandung students in participating in writing competitions. Although there was an increase in the literacy of SMPN 39 Bandung students, students' reading and writing interests must be increased again as seen from the results of the student reading interest instrument.